2004
DOI: 10.1021/ja048548j
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, Hemolysis, and Acute in Vivo Toxicity of Dendrimers Based on Melamine, Candidate Vehicles for Drug Delivery

Abstract: A small library of dendrimers was prepared from a common precursor that is available in 5 g scale in five linear steps at 56% overall yield. The precursor is a generation three dendrimer that displays 48 peripheral sites by incorporating AB4 surface groups. Manipulation of these sites provided six dendrimers that vary in the chemistry of the surface group (amine, guanidine, carboxylate, sulfonate, phosphonate, and PEGylated) that were evaluated for hemolytic potential and cytotoxicity. Cationic dendrimers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
220
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 383 publications
(235 citation statements)
references
References 29 publications
(19 reference statements)
9
220
1
1
Order By: Relevance
“…However, when using piperazine, dimerization of monochlorotriazines was observed under non-ideal reaction conditions that were usually attributed to concentration, rate of addition, ineffective stirring or lack thereof, temperature of addition and the magnitude of stoichiometric excess. 4,[8][9][10][11][12][13][14][15][16][17][18] Reactions with either p-aminobenzylamine or piperazine could be readily followed by NMR. The shift of the benzylic protons on reaction with the monochlorotriazine dendron or the desymmetrization of methylene groups of the piperazine group were diagnostic.…”
mentioning
confidence: 99%
“…However, when using piperazine, dimerization of monochlorotriazines was observed under non-ideal reaction conditions that were usually attributed to concentration, rate of addition, ineffective stirring or lack thereof, temperature of addition and the magnitude of stoichiometric excess. 4,[8][9][10][11][12][13][14][15][16][17][18] Reactions with either p-aminobenzylamine or piperazine could be readily followed by NMR. The shift of the benzylic protons on reaction with the monochlorotriazine dendron or the desymmetrization of methylene groups of the piperazine group were diagnostic.…”
mentioning
confidence: 99%
“…88 The results of the cell viability study indicated that the neutral dendrimer decorated with PEG, 80, was the least hemolytic over a concentration range of 0.001-10 mg/mL. Subsequent acute dosing experiments with the PEG-functionalized dendrimer indicated no toxicity in mice at concentrations up to 2.56 g/kg (intraperitoneal administration) or 1.28 g/kg (intravenous administration).…”
Section: Biologically Relevant Moleculesmentioning
confidence: 97%
“…1 N, γ-H), 1.39 (s, 108H, C(CH 3 ) 3 ). 13 G3-Cl-A solution of G3-NH 2 (0.234 g, 0.0794 mmol), DIPEA (0.43 mL, 2.86 mmol) and 1 (0.914 g, 1.9 mmol) was prepared in a CH 2 Cl 2 (50 mL)-EtOAc (15 mL)-water (5 mL) mixture to give a slurry. The solution was stirred at 25 °C for 16 h, the solvents removed in vacuo and the residue taken up in 50 mL CH 2 Cl 2 .…”
Section: G2-cl-a Solution Of G1-nhmentioning
confidence: 99%
“…1 H NMR (300 MHz, CDCl 3 ) δ 9.33, 5.62, 4.98 (br, 42H, NH), 3.75 (br, 24H, CH 2 , piperazine), 3.65-3.52 (br, 120H, NCH 2 and C 5 H 10 N, α-H), 3.36-3.29 (br, 36H, CH 2 NH-C 3 N 3 ), 3.03 (br, 48H, CH 2 NHBoc), 1.89 (br, 12H, G1-NCH 2 CH 2 ), 1.79 (br, 24H, G2-NCH 2 CH 2 ), 1.68 (br, 48H, G3-NCH 2 CH 2 ), 1.49 (br, 54H, C 5 H 10 N, β-H and γ-H), 1.39 (s, 108H, C(CH 3 ) 3 ), 1.37 (s, 108H, C(CH 3 ) 3 ). 13 G3-Pip-A clear solution of G3-Cl (0.66 g, 0.080 mmol) and piperidine (0.316 mL, 3.19 mmol) was prepared in THF (30 mL). The mixture was stirred at 25 °C for 12 h, and the resulting slurry was filtered through silica to give a clear solution.…”
Section: G2-cl-a Solution Of G1-nhmentioning
confidence: 99%